Schwarzenberger bundles on smooth projective varieties - Arrondo, E.; Marchesi, S.; Soares, H. (Journal of Pure and Applied Algebra, 2016)
We define Schwarzenberger bundles on smooth projective varieties and we introduce the notions of jumping subspaces and jumping pairs of (F-0, O-X)-Steiner bundles. We determine a bound for the dimension of the set of jumping pairs. We classify those Steiner bundles whose set of jumping pairs has maximal dimension by proving that they are Schwarzenberger bundles.